Requalificação urbana no Rio de Janeiro, RJ, Brasil: o projeto porto maravilha e suas implicações - Paulo, Felipe Eduardo Portela de (2024)
Introduction: The Porto Maravilha Project, launched in 2009 in Rio de Janeiro, aimed to revitalize the port region for international sporting events, involving companies such as Odebrecht and OAS, in partnership with the federal and state governments. However, criticism has arisen due to the lack of affordable housing, gentrification and lack of transparency. Given this, it is important to analyze the studies carried out to date to summarize their content, identify gaps and interpret their results. Objective: The objective of this dissertation is to analyze the impacts attributed to the Porto Maravilha Project, from the perspective of neoliberal urbanism, in the port region of Rio de Janeiro, RJ, Brazil. Methodology: The research, classified as exploratory and qualitative, used a systematic literature review with content analysis and bibliometrics, based on 84 articles selected from the Web of Science, Scopus and Scielo bibliographic databases. Results: The results reveal complex impacts, such as touristification of the region, facing challenges such as gentrification and social exclusion. The neoliberal approach is reflected in the financialization of urban space, generating tensions between financial profit and social justice. Regarding historical-cultural aspects, the project promotes and preserves cultural heritage, but raises concerns about the dilution of the history of slavery and exclusion of marginalized narratives. Conclusion: It is concluded that the Porto Maravilha Project significantly impacted the region, involving financial, real estate and social aspects. However, there is a gap regarding the effective participation of the local population in project shaping and a scarcity of studies on regulatory documentation and community perception. Future studies are suggested that incorporate more participatory methodological approaches for a more comprehensive understanding of the project's impacts.